MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN AGAMA ISLAM - Ulfia Ustina; Abdullah Arief Cholil; Ali Bowo Tjahjono (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study was to uncover how the principal's management in improving the quality of Islamic education. This research was conducted at Fathul Huda Middle School Sidorejo Sayung Demak. This type of research is field research using descriptive qualitative analysis research method, namely researchers observing and interacting directly with the principal, Islamic religious education teachers, administrative heads, Waka for the quality and development of human resources, Assistant Principal of Academic curriculum, and Assistant Principal of infrastructure facilities in junior high school Fathul Huda, Sidorejo, Sayung, Demak.  This research used interview methods for, observation and collecting data documentation. Results showed that the administrative management of the principal in improving the quality of Islamic education has been implemented effectively, indicated by all elements of administrative management already running according to the program ranging from planning to supervision. The operative management of the principal in improving the quality of Islamic education has been implemented effectively, which is indicated by all elements of operative management running functionally.Keywords: Islamic education quality, management, principal